Assessment of genetic diversity in sea buckthorn (Hippophae rhamnoides L.) accessions from Mongolia based on RAPD markers - Sandag, Zolzaya; Balchin, Dorjderem; Enkhtuya, Ariya; Myagmar, Nomin; Oyunbat, Nomuun; Buyanbat, Khurelsukh; Batnasan, Sosorburam; Badam, Ninj; Sandagdorj, Jamiyansuren; Tsendsuren, Oyunsuren; Davaakhuu, Gantulga (Proceedings of the Mongolian Academy of Sciences, 2021)
Hippophae rhamnoides L., which belongs to the Elaegnaceae family, is one of the medically and environmentally valuable berry crops with its high nutritious and bioactive compounds. Despite its high demand in the food, medicinal and agricultural industries, this species has been less studied molecularly. In view of this, an effort has been made in the present study to characterize 24 accessions of H. rhamnoides collected from different geographical regions of Mongoliaa through random amplified polymorphic DNA (RAPD) markers. A total of 10 RAPD primers were used in the present study for their ability to produce clear, scorable amplicons. The RAPD analysis totally generated 87 bands, of which 84 (96.34%) were polymorphic, pointing to a high degree of genetic variation. The similarity coefficient ranged from 0.4-1 with the mean of 0.78. The UPGMA dendrogram was generated using these data grouped accessions into two main clusters. Cluster analysis reflected a relatively close relationship between accessions grown at the same or neighbouring areas. Thus, our data could be informative for further selection and management of germplasm collections and crossing strategies for sea buckthorn.